KAJIAN TEORI FORMALISME DAN STRUKTURALISME - Fadlil Munawwar Manshur (SASDAYA: Gadjah Mada Journal of Humanities, 2019)
From the perspective of formalism theory, this study aims to reveal that a research on literary texts does not only pay attention to textual facts existing in literary works, but also needs to pay attention to what exists outside the text. In the literary works, the element of defamiliarization holds that literary language is able to express facts of stories using unfamiliar languages. From the perspective of structuralism theory, this study aims to reveal that structuralism is conceptually a continuation of formalism which largely depends on language. Structuralism theory has a close relationship with linguistics, especially in analyzing the functions of the language used. The analysis of language function can help understanding language semiotics that views literature as a sign that then led to literary semiotics. Therefore, functioning to examine a phenomenon, the concept of semiotic structuralism emerged as a social fact.  Critical approach was deemed suitable to be used in this study because formalism theory and structuralism theory are part of a social construction and part of a discursive formation in the formation of subject and reality. As a result, it could be seen the position of formalism theory and structuralism theory in literary research of which raw material is language. The findings in this study are that the formalism theory in its development is dynamic and its language construction stimulates readers to respond. In principle, literary work is not autonomous because it contains author’s feelings and society’s mind. Literary research should exceed the boundaries of formalism and be able to create new vocabularies in writing novels. In the novel, there is intertextual polyvalence, which is a series and intensive dialogic linkages that are capable of giving birth to new novels. Another finding is that structuralism theory has a close relationship with linguistics, for example phonological elements in linguistics which can help literary theory in analyzing sound levels in oral literary works. This theory has also developed a study of poetry to the aesthetic level so that this study has shifted from its original aspects of verbal art only to all art and artistic aesthetics in the present time. This shift distinguishes the views between formalism and structuralism in relation to norms and values inherent in language.